Консолидација повериоца и дужника. Confusio у римском праву и у Аустријском грађанском законику (ABGB) - Binder, Michael (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
In both Roman law and Austrian civil law, there is a question regarding whether a consolidation between a creditor and his debtor leads to an expiration of the creditor’s claim and the debtor’s obligation. The following article focuses on legal relationships in which more than two parties are involved, meaning it would still be possible for the creditor (or his heir) to raise a claim against the debtor. Firstly, it is necessary to analyse a case from the Roman jurist Paulus (D. 46, 1, 71 pr.). Following this analysis, the legal situation in Roman law is compared to that in Austrian civil law.